ANALYSIS OF FACTORS ASSOCIATED WITH ACHIEVEMENTS OF COVID-19 VACCINATION IN THE ELDERLY AT THE GUNTUNG PAYUNG.docx - Rahmatullah, Mohammad Dede; Adhani, Rosihan; Nugroho, Adi; Suharton, Eko; Rahman, Fauzie (Jurnal Ilmiah Wahana Pendidikan, 2023)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2), a new type of coronavirus discovered in humans since an extraordinary incident appeared in Wuhan China in December 2019, and causes disease Coronavirus Disease-2019 (COVID- 19). Achievement of COVID-19 vaccination in Indonesia national elderly on July 10 2023 dose 1 84.88%, dose 2 70.33%, dose 3 33.75% and dose 4 2.15%. The achievement of vaccination for the elderly in South Kalimantan Province dose 1 was 86.52%, dose 2 was 63.10%, dose 3 was 23.74%, and dose 4 was 0.75% while the achievement of COVID-19 vaccination in the elderly in Banjarbaru city dose 1 was 11,349 doses , dose 2 was 9,876 doses, dose 3 was 5,567 doses, and dose 4 was 347 doses. To speed up the achievement, the government is actively providing vaccination services through the Puskesmas and public spaces. Knowing the relationship between comorbid diseases, elderly independence, perceptions of government policiesrelated to Covid-19 vaccination, the ease of obtaining vaccine information with Access to COVID-19 Vaccination in the elderly group at the Guntung Payung Health Center, Banjarbaru City. Results of analysis with Who squaresshows the p-value of comorbid diseases (p= 0.000), elderly independence (p = 0.015), perceptions of government policiesrelated to COVID-19 vaccination(p=0.031), and ease of obtaining vaccine information (p=0.007). The results of the analysis with multiple logistic regression showed the p value and Exp B of the comorbid disease variable (p = 0.003, Exp B =3,064), elderly independence variable (p=0.026, Exp B=2,253), the variable perception of government policy (p=0.028, Exp B= 2.240), and ease of obtaining vaccine information (p=0.024, Exp B= 2.541). The results of the analysis with Chi square showed p values of age (p= 0,026), gender (p= 0,017), JKN membership status (p= 0,013), toothbrush behavior (p=0,006) and cariogenic food comsumption (p=0,001). The results of analysis with multiple logistic regression showed values of p and Exp B of age (p=0,008, Exp B=2,569), gender (p=0,017, Exp B= 1,956), JKN membership status (p=0,031, Exp B= 1,667), toothbrush behavior (p=0,006, Exp B= 2,742), and cariogenic food consumption (p=0,006, Exp B= 2,952) There is a significant relationship between comorbid diseases, elderly independence, perception of government policies, ease of obtaining vaccine information and access to COVID-19 vaccination in the elderly group at the Guntung Payung Health Center, Banjarbaru City. Themost dominant variable related is comorbid disease.